Molecular markers of neuroendocrine function and mitochondrial biogenesis associated with early life stress - Ridout, Kathryn K.; Coe, Jesse L.; Parade, Stephanie H.; Marsit, Carmen J.; Kao, Hung-Teh; Porton, Barbara; Carpenter, Linda L.; Price, Lawrence H.; Tyrka, Audrey R. (Psychoneuroendocrinology, 2020)
•Methylation of the glucocorticoid receptor promotor region (NR3C1) significantly mediated the relation between early adversity and mitochondrial DNA copy number (mtDNAcn).•This result suggests NR3C1 methylation may be an important mechanism linking early adversity and changes in mtDNAcn, a marker of cellular energy metabolism.•There was a positive association between early adversity and mtDNAcn, and negative associations of early adversity with NR3C1 methylation and NR3C1 methylation with mtDNAcn. Glucocorticoid receptor gene (NR3C1) promoter methylation influences cellular expression of the glucocorticoid receptor and is a proposed mechanism by which early life stress impacts neuroendocrine function. Mitochondria are sensitive and responsive to neuroendocrine stress signaling through the glucocorticoid receptor, and recent evidence with this sample and others shows that mitochondrial DNA copy number (mtDNAcn) is increased in adults with a history of early stress. No prior work has examined the role of NR3C1 methylation in the association between early life stress and mtDNAcn alterations. Adult participants (n = 290) completed diagnostic interviews and questionnaires characterizing early stress and lifetime psychiatric symptoms. Medical conditions, active substance abuse, and prescription medications other than oral contraceptives were exclusionary. Subjects with a history of lifetime bipolar, obsessive-compulsive, or psychotic disorders were excluded; individuals with other forms of major psychopathology were included. Whole blood mtDNAcn was measured using qPCR; NR3C1 methylation was measured via pyrosequencing. Multiple regression and bootstrapping procedures tested NR3C1 methylation as a mediator of effects of early stress on mtDNAcn. The positive association between early adversity and mtDNAcn (p = .02) was mediated by negative associations of early adversity with NR3C1 methylation (p = .02) and NR3C1 methylation with mtDNAcn (p < .001). The indirect effect involving early adversity, NR3C1 methylation, and mtDNAcn was significant (95 % CI [.002, .030]). NR3C1 methylation significantly mediates the association between early stress and mtDNAcn, suggesting that glucocorticoid receptor signaling may be a mechanistic pathway underlying mtDNAcn alterations of interest for future longitudinal work.